Selected Papers of Michael G Rossmann With Commentaries 2014
DOI: 10.1142/9789814513357_0037
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Dengue Virus: Implications for Flavivirus Organization, Maturation, and Fusion

Abstract: SummaryThe first structure of a flavivirus has been determined by using a comThe first structure of a flavivirus has been determined by using a combination of cryoelectron microscopy and fitting of the known structure of glycoprotein E into the electron density map. The virus core, within a lipid bilayer, has a less-ordered structure than the external, icosahedral scaffold of 90 glycoprotein E dimers. The three E monomers per icosahedral asymmetric unit do not have quasiequivalent symmetric environments. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
319
0
13

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(340 citation statements)
references
References 13 publications
6
319
0
13
Order By: Relevance
“…Similar peptides also induce mitochondrial membrane permeability, although the relevance of this to natural infection is unclear (Catteau et al, 2003). Single-TMD topology has also been predicted for M, implying that two membrane-associated forms may exist, potentially as a result of the tight turn (3 aa) between the two TMDs found within particles (Kuhn et al, 2002;Yu et al, 2008;Zhang et al, 2003). Much like Vpu and 6K, investigators are yet to assign a functional role to potential M-mediated channel activity, although mutation of a highly conserved His39 in the first TMD reduced dengue virus spread without affecting polyprotein processing or the formation of prM-E heterodimers, yet this did prevent glycoprotein secretion, which may conceivably relate to channel-forming activity (Pryor et al, 2004).…”
Section: Flavivirus M Proteinmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar peptides also induce mitochondrial membrane permeability, although the relevance of this to natural infection is unclear (Catteau et al, 2003). Single-TMD topology has also been predicted for M, implying that two membrane-associated forms may exist, potentially as a result of the tight turn (3 aa) between the two TMDs found within particles (Kuhn et al, 2002;Yu et al, 2008;Zhang et al, 2003). Much like Vpu and 6K, investigators are yet to assign a functional role to potential M-mediated channel activity, although mutation of a highly conserved His39 in the first TMD reduced dengue virus spread without affecting polyprotein processing or the formation of prM-E heterodimers, yet this did prevent glycoprotein secretion, which may conceivably relate to channel-forming activity (Pryor et al, 2004).…”
Section: Flavivirus M Proteinmentioning
confidence: 91%
“…The 75 aa small M (membrane) protein is cleaved from the viral E protein by signal peptidase as a prM precursor, which is then processed in the Golgi and acidifying secretory compartments by furinlike proteases into M and the pr peptide (Junjhon et al, 2008;Keelapang et al, 2004;Kuhn et al, 2002;Wong et al, 2012;Yu et al, 2008). The release of virions from the cell surface results in the loss of pr and resultant formation of a mature, infectious virion (Junjhon et al, 2008(Junjhon et al, , 2010Yu et al, 2008Yu et al, , 2009.…”
Section: Flavivirus M Proteinmentioning
confidence: 99%
“…Differences in the crystal structures of the BVDV1 and HCV E2 glycoproteins illustrate that common genome arrangement among members of the Flaviviridae family does not translate to structurally similar fusion glycoproteins (29,30). Conversely, structural comparisons indicate that sequences showing marginal homology can display a common class II fold (e.g., dengue virus E and Semliki Forest virus E1 proteins) (37,38). It has been suggested that the use of arthropod vectors may require conservation of the class II fold by distant members of the Togaviridae and Flaviviridae families, while phylogenetically closer viruses that strictly infect mammals may have evolved to develop specialized entry machineries (39).…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to a family of Flaviviruses (which also includes the Dengue, yellow fever and West Nile viruses), a single stranded, positive-sense RNA virus with a 10.7 Kb genome encoding a single polyprotein that is cleaved into three structural proteins (C, precursor M/M, and E) and seven non-structural [67]. The envelope of Flaviviruses, determined by cryo-electron microscopy, was shown to be made up of 180 copies of two different proteins, the envelope (E) protein and membrane (M) protein, in which 90 E dimers completely cover the viral surface [68,69]. E protein is a glycoprotein responsible for virus entry, representing a major target of neutralizing antibodies for Flaviviruses, including Zika virus, Dengue virus, and other mosquito-transmitted viruses from the same family, was shown to bind to DC-SIGN via the glycans on E proteins of the mature virion [70].…”
Section: Zika Virusmentioning
confidence: 99%